Detecting Cyber Attacks Using Anomaly Detection with Explanations and Expert Feedback - Siddiqui, Amran; Stokes, Jay; Seifert, Christian; Argyle, Evan; McCann, Robert; Neil, Joshua; Carroll, Justin (2019 International Conference on Acoustics, Speech, and Signal Processing, 2019)
Detecting cyber attacks in large computer networks is crucial for many organizations. To that purpose, different types of detectors capture the important signals resembling a security attack from individual computers and bring that to the attention of a security analyst. Unfortunately, the analyst sometimes has no indications about why the particular computer was identified as being "under attack". In addition, the analyst may have no method to provide feedback to the detector if the computer was actually identified for some benign reason. In this paper, we use a state-of-the-art anomaly detector called an Isolation Forest [1] for attack detection and generate explanations about why the detector identified certain computers as anomalous. These explanations allow the analyst to direct their investigation in order to save time. We then take the feedback from the analyst in the form of true and false positives and update the anomaly detector to capture signals that align better with the given feedback. Our experiments on actual network data show that the explanations give more insight into the detections, and the analyst’s feedback increases the attack detection rate.